TEACHER BURNOUT AND PROFESSIONAL STRESS - VASILE RADU PREDA (Studia Universitatis Babes-Bolyai, 2011)
ABSTRACT. Professional exhaustion ("burnout") is the result of chronic stressful conditions and of the feeling that at the work-place there is a discrepancy between personal abilities and the real working conditions. The objective of this study is a research of the level of perceived stress in case of teachers and that of dimensions professional exhaustion a) the connection between the level of perceived stress and that of emotional exhaustion; b) the connection between the level of perceived stress and that of the depersonalization at the level of interpersonal relations.